Peningkatan Prestasi Belajar IPA melalui Strategi Peta Konsep pada Siswa Kelas VII-A SMPN 1 Lenek Semester II Tahun Pelajaran 2020/2021 - Kusdiningsih, Trini (YASIN, 2021)
This study aims to determine the improvement of Integrated Science learning outcomes by applying the Concept Map Strategy. This research is a type of classroom action research conducted in class VII-A of SMPN 2 Aikmel. Data collection was carried out by experiments, observations, tests, documentation, and interviews. Data on learning outcomes and student participation in learning were analyzed using comparative descriptive techniques, namely by comparing research results obtained between cycles, while learning implementation data were analyzed using critical analysis techniques, namely by revealing the weaknesses and strengths of the performance displayed by the teacher in the implementation of activities during action. The results of the analysis show that student learning outcomes have increased, this can be seen from the test results data, the cycles have increased. Classical completeness in the first cycle of 65% increased to 91% in the second cycle, meaning that there was an increase in learning outcomes of 26%. Besides learning outcomes, there was also an increase in student activity from the first cycle, an average of 2.85 (moderately active category) and an increase in the second cycle of 4.05 (active category) this means that there was an increase in student activity of 1.2.